Different approaches to system science - Svítek Miroslav; Žák Ladislav (Annals of Mathematics and Physics - Peertechz Publications, 2022)
The goal of the paper is to present a new definition of a holistic approach to the description of complex systems including features such as emergent behavior, exaptation, contingency, self-organization, etc. The presented approach is based on concepts such as singularity (internal behavior of a partial system component without any links), duality (analyses of links between pairs of system components) and a plurality (links between clusters of system components). Energetics is presented as a new science (third-order cybernetics) using the results of the theory of complex systems connected with the algorithms of artificial intelligence so that a better coexistence between humans and machines occurs.